New Insights in the Genetics and Genomics of Adrenocortical Tumors and Pheochromocytomas - Igaz, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book includes 17 papers published in the Special Issue/Article Collectoin "New Insights in the Genetics and Genomics of adrenocortical tumors and pheochromocytomas" including an editorial, 10 research papers and six review articles. Adrenal tumors represent a hot topic in contemporary endocrine oncology. Significant advancements in the genetics of genomics of these tumors have been made in recent years, and these articles give a useful and comprehensive overview of these issues. Questions regarding molecular pathogenesis, diagnosis (biomarkers) and even treatment are discussed in the papers written by international leaders of the field. Manuscripts are focused on three main topics: i. primary aldosteronism (the most common cause of secondary endocrine hypertension), ii. adrenocortical cancer and iii. pheochromocytoma/paraganglioma, which are the tumors with the highest heritability in humans. The book is edited by Prof. Peter Igaz (Department of Endocrinology, Faculty of Medicine, Semmelweis University).